2022
DOI: 10.1021/acs.chemmater.1c04105
|View full text |Cite
|
Sign up to set email alerts
|

NaGdS2: A Promising Sulfide for Cryogenic Magnetic Cooling

Abstract: The development of effective and eco-friendly cooling technology demands an investigation of new magnetocaloric materials. Compounds containing gadolinium are one of the best candidates due to the large spin-only magnetic moment of Gd 3+ ion. This work reports on the magnetocaloric properties of the AGdS2 family (A = Li, Na, K, Rb) in relation to crystal chemistry of these compounds. These sulfides crystallize in two different structure-types: NaCl (A = Li) and -NaFeO2 (A = Na, K, Rb). Although one would expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 81 publications
1
17
0
Order By: Relevance
“…This is rationalized by differences in the exchange interaction and the onset of ordering at higher temperatures in LiGdS 2 . At high temperatures, T > 2 K, a similar effect is not observed in the A 2 GdSbO 6 double perovskites but may result in significant differences in the magnetocaloric effect closer to the ordering temperature in Ca 2 GdSbO 6 …”
Section: Comparison To Top Performing Gd3+ Magnetocaloric Materialsmentioning
confidence: 72%
See 1 more Smart Citation
“…This is rationalized by differences in the exchange interaction and the onset of ordering at higher temperatures in LiGdS 2 . At high temperatures, T > 2 K, a similar effect is not observed in the A 2 GdSbO 6 double perovskites but may result in significant differences in the magnetocaloric effect closer to the ordering temperature in Ca 2 GdSbO 6 …”
Section: Comparison To Top Performing Gd3+ Magnetocaloric Materialsmentioning
confidence: 72%
“…At high temperatures, T > 2 K, a similar effect is not observed in the A 2 GdSbO 6 double perovskites but may result in significant differences in the magnetocaloric effect closer to the ordering temperature in Ca 2 GdSbO 6 . 44 …”
Section: Comparison To Top Performing Gd 3+ Magnet...mentioning
confidence: 99%
“…For instance, FeCr 2 S 4 presents a reversible MCE around a FiM transition (T N = 167 K) with maximum magnetic entropy change = 3.72 J.kg -1 .K -1 for ΔH = 50 kOe, along with 𝛥𝑆 𝑚𝑎𝑥 a cusp-like anomaly around 70 K 4 . Recently, Delacotte et al 19 showed a larger MCE for NaGdS 2 that presents very weak local AFM interactions because of its negligible exchange interactions. Such a compound exhibits a up to 54 J kg -1 K -1 at 2.5 K for μ 0 ΔH = 5 T, being then suggested 𝛥𝑆 𝑚𝑎𝑥 𝑀 as a promising material for Cryogenic Magnetic Cooling.…”
Section: Introductionmentioning
confidence: 99%
“…At high temperatures, T > 2 K, a similar effect is not observed in the A 2 GdSbO 6 double perovskites but may result in significant differences in the magnetocaloric effect closer to the ordering temperature in Ca 2 GdSbO 6 . 44 The fcc materials presented here, Ba 2 GdSbO 6 and Sr 2 GdSbO 6 , are likely able to cool below the industry standard, Gd 3 Ga 5 O 12 (which has a lower cooling limit of ∼ 0.8 K due to spin-spin correlations 45 ), into the temperature regime of paramagnetic salts (∼ 100 mK or less 46 ) based on their minimal superexchange. This presents a possible significant advancement as the frus-trating lattice should have a better per unit volume magnetic entropy change than a Gd 3+based paramagnetic salt.…”
Section: Comparison To Top Performing Gd 3+ Magnetocaloric Materialsmentioning
confidence: 87%